Acute issues in the pharmacotherapy of hand osteoarthritis - O. A. Gromova; I. Yu. Torshin; A. V. Naumov; L. V. Vasilyeva; Ye. F. Yevstratova; А. N. Gromov (Фармакоэкономика, 2021)
The article focuses on the review of a pharmacotherapeutic approach to the therapy of hand osteoarthritis (HO). Apart from non-steroid antiinflammatory drugs (NSAID), promising therapeutic means of HO therapy include steroid drugs, chondroitin sulfate (CS), glucosamine sulfate (GS), and vitamin D. Transdermal application of NSAID and steroid drugs reduces the side effects without a decrease in the effectiveness of the therapy. Reconstructive therapy of cartilaginous and connective tissue of hands includes a long-term application of CS/GS, and in the acute period, injections of CS/GS.